2007
DOI: 10.1177/0269216307077328
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function during parenteral opioid titration for cancer pain

Abstract: Parenteral opioid titration for relief of cancer pain was not associated with respiratory depression as demonstrated by significant changes in ET-CO(2) or oxygen saturation in non-oxygen dependent cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 15 publications
(18 reference statements)
2
23
0
1
Order By: Relevance
“…Appropriately titrated, opioids are safe and do not cause clinically significant respiratory depression. 41 Allen et al 42 showed that an opioid in low doses (diamorphine 2.5 mg subcutaneously) was effective and well tolerated in elderly patients with advanced pulmonary fibrosis who had not received opioids before.…”
Section: Look For Potentially Reversible Causes Of Nausea and Vomitingmentioning
confidence: 99%
“…Appropriately titrated, opioids are safe and do not cause clinically significant respiratory depression. 41 Allen et al 42 showed that an opioid in low doses (diamorphine 2.5 mg subcutaneously) was effective and well tolerated in elderly patients with advanced pulmonary fibrosis who had not received opioids before.…”
Section: Look For Potentially Reversible Causes Of Nausea and Vomitingmentioning
confidence: 99%
“…Indeed, a common misconception is that opioid use will hasten death through respiratory depression, 38 although there is little evidence to support this belief when the drugs are appropriately titrated. 11,39,40 Reid et al 37 found that some cancer patients perceived opioids as a "last resort" for pain control and thus interpreted their physicians' offer of morphine for pain relief as a signal that death was near, rejecting the opioid as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Atemdepression bei Tumorschmerz kann durch Opioidtitration vermieden werden [26]. Die Individualisierung der Schmerztherapie ist die Grundlage für die Tumorschmerztherapie [27].…”
Section: Dosis -Titrationunclassified